Exploring the Dimensions of Intercultural Communicative Competence (ICC) in English Learning: Insights from EFL Students - Fadhlan Saini; Andi Anugrah Surya Ardhy (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Intercultural communication competence is now required in such higher education institutions. The issue can be seen by having misconceptions, misunderstandings, and a need for knowledge to understand other cultural exchanges like English and Indonesia. It happened in IAIN Manado, where the researcher takes place as the case of the study and as the research location. Respondents in this study were 28 students of the Manado IAIN English Education Study Program. The data collection technique used in this study was purposive sampling and analyzed through descriptive qualitative analysis. It is analyzed by reducing data, selecting relevant data, organizing data into regular patterns, and drawing conclusions. The study results show that learning English that integrates intercultural communicative competence positively benefits students, with an average percentage of 73.95. An effective strategy for combining intercultural communication competencies is openness to experience and knowledge of other cultures. However, in combining intercultural communication competencies, students also face challenges. These challenges include adapting to foreign cultural communication styles, expressing opinions in the context of intercultural communication in English, understanding conversational etiquette in foreign cultures, and socializing with new cultural environments while learning English. Then, with the right approach and sufficient hands-on experience, students can overcome these challenges and develop solid intercultural communication skills.